Map Matching Algorithm for the ”Spar på farten” Intelligent Speed Adaptation Project - Tradisauskas, Nerius; Juhl, Jens; Lahrmann, Harry; Jensen, Chrisitan S. (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
The availability of Global Navigation Satellite Systems (GNSS) enables sophisticated vehicle guidance and advisory systems such as Intelligent Speed Adaptation (ISA) systems. In ISA systems, it is essential to be able to position vehicles within a road network. Because digital road networks as well as GNSS positioning are often inaccurate, a technique known as map matching is needed that aims to use this inaccurate data for determining a vehicle’s real road-network position. Then, knowing this position, an ISA system can compare speed with the speed limit in effect and take measures against speeding. This paper presents an online map matching algorithm with an extensive number of weighting parameters that allow better determination of a vehicle’s road network position. The algorithm uses certainty value to express its belief in the correctness of its results. The algorithm was designed and implemented to be used in the large scale ISA project ”Spar på farten” . Using test data and data collected from project participants, the algorithm’s performance is evaluated. It is shown that algorithm performs correctly 95 % of the time and is capable of handling GNSS positioning errors in a conservative manner.